What’s Keeping Public Library Trustees Up at Night? - Clark, Deborah; Smith, Jenny (Maine Policy Review, 2024)
Maine public library boards take on the crucial responsibility of overseeing the functioning and sustainability of our local libraries. These trustee volunteers guide their organizations’ services and ensure their financial sustainability. In a recent survey conducted, we found these library trustees are greatly concerned with maintaining adequate funding to address increased community, facility, and staffing challenges. Most community libraries are funded entirely at the local level . As our public libraries strive to meet the expanding social, educational, health, and economic needs of community members, Maine residents must find innovative ways to provide consistent direct state and federal funding to support these service organizations without adding to their already over-burdened operations.